Um olhar sobre a produção científica do campo da Pedagogia: o que dizem as dissertações e teses nos anos de 2002 a 2012 - Magna Bonifácio de Araújo, Regina; Imaculada Lucinda, Nilzilene (Revista Vozes dos Vales: Publicações Acadêmicas, 2014)
The article discusses the state of knowledge of scientific production in the field of pedagogy held from dissertations and theses from 2002 to 2012. Displays the objects of study, subjects addressed, methodological approach, instruments and sources of data collection and leaned on Ferreira (2002); Romanowiski and Ens (2006); Haddad (2002); Ribeiro (2011). We identified 49 studies with the themes: knowledge and identity; significance of Pedagogy; curriculum; work not in school; national curriculum guidelines, management; training and practice. Initial training was further investigated themes and maintained a close relationship with the themes identity and curriculum. The study revealed that the subject was not underused school spaces indicating the need for further studies and pointed out that narrative research, oral history and life is gaining relevance.